Electronic Circuit Design for Hydrogen Ion Measurement System - Arfeen, Ibrahim Elkhier Hussien (Gezira Journal of Engineering and Applied Sciences; Vol 7 No 2 (2012), 2018)
This paper aims to study electronic design circuit for the hydrogen ion measurement system in chemical analysis and environment fields, to detect the pH of the subjected solution. Electronic design building up on operational amplifiers LM 324 and LF444. The practical experiment is done by glass electrode transducer. The design has been tested and calibrate by four standard buffer solutions and five kinds of aqueous solution. These four standard solutions (pH 4, pH 7, pH 9.2 and pH 10) were intended to cover the range for detection of acidity or alkalinity value through out the measuring range and obtained the desired results. The results obtained by electronic design are reasonable when compared to other pH meter system